THE UTILIZATION OF ENGLISH VIDEOS IN ESL TEACHING AND LEARNING - Narbekova, Ra’no Usmanovna (INTERNATIONAL CONFERENCES, 2023)
The main attention of the article is focused on the benefits and goals of using authentic video materials for language learning and teaching, as well as the advantages of using videos at the English language lessons.